Overcoming barriers to care for individuals with fetal alcohol spectrum disorder: challenges and solutions in New Mexico and beyond - Gibson, Aubrey C.; Velhagen, Juliet M.; Jaffe, Talya; Hill, Dina E.; Moriarta, Marcia L.; Valenzuela, C. Fernando (Frontiers in Pediatrics, 2025)
Fetal Alcohol Spectrum Disorder (FASD) encompasses a range of neurodevelopmental impairments caused by prenatal alcohol exposure, affecting cognitive, behavioral, and social functioning. Despite its high prevalence, FASD remains underdiagnosed, particularly in regions like New Mexico (NM), where high rates of alcohol use, poverty, and unplanned pregnancies exacerbate the burden of the disorder. Individuals with FASD often face significant challenges in adaptive functioning, education, and social integration, with many experiencing adverse childhood events that compound developmental difficulties. Access to appropriate healthcare and social services is hindered by diagnostic complexity, stigma, and exclusion from disability benefits. Limited awareness among healthcare providers, educators, and social workers further impedes early intervention, leading to increased risks of poor academic performance, unemployment, homelessness, and criminal justice involvement. Specialized FASD clinics play a critical role in diagnosis and support, but remain insufficient to meet the needs of affected individuals. Expanding education, advocacy, and tailored support services is essential to addressing these gaps. By enhancing awareness, integrating FASD-specific disability benefits, and strengthening community-based programs, long-term outcomes for individuals with FASD can be significantly improved.